Does phonological encoding in speech production always follow the retrieval of semantic knowledge?: Electrophysiological evidence for parallel processing - Abdel Rahman, Rasha; Sommer, Werner (Brain research. Cognitive brain research, 2003)
In this article a new approach to the distinction between serial/contingent and parallel/independent processing in the human cognitive system is applied to semantic knowledge retrieval and phonological encoding of the word form in picture naming. In two-choice go/nogo tasks pictures of objects were manually classified on the basis of semantic and phonological information. An additional manipulation of the duration of the faster and presumably mediating process (semantic retrieval) allowed to derive differential predictions from the two alternative models. These predictions were tested with two event-related brain potentials (ERPs), the lateralized readiness potential (LRP) and the N200. The findings indicate that phonological encoding can proceed in parallel to the retrieval of semantic features. A suggestion is made how to accommodate these findings with models of speech production.